IMPLEMENTASI PENGELOLAAN DANA WAKAF TUNAI PADA KOPERASI MASJID SABILILLAH - Maghfiroh, ElliyaS yahfira; Ananda, Candra Fajri (Islamic Economics and finance in Focus, 2022)
Cash waqf is an Islamic platinum philanthropy having substantial roles in both economic and social developments of community. At the Sabilillah Mosque Cooperatives of Malang, this type of Islamic endowment builds and develops the economic potential and capacity of its members in particular and the community in general to improve social welfare. This socio legal research addresses how the cooperative manages the endowment and how the management conforms the Islamic law using a descriptive qualitative approach. The data was harvested through interviews and documentation, which is collecting, compiling, and managing relevant data. This study finds that the waqf is managed by carrying out the membership procedures applied by the cooperative, i.e. paying compulsory deposit, principal deposit, administration fee, and the cash waqf. The cooperative allocates the waqf fund only for public welfare, i.e. loan and saving system, such as financing businesses, paying school fees, helping people to pay their loan, and so on.